SALIVARY SECRETORY IMMUNOGLOBULIN A LEVEL OF CHILDREN WITH ACUTE LYMPHOBLASTIC LEUKEMIA IN MAINTENANCE PHASE - Rani, Danar Pradipta; Budiardjo, Sarworini B; Suharsini, Margaretha (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this research is to investigate the differences in salivary secretory immunoglobulin A (sIgA) levels between children with gingivitis who have acute lymphoblastic leukemia (ALL) and are in the maintenance phase of chemotherapy and the levels in healthy children with gingivitis. Methods: This study used cross-sectional and laboratory observation methods with 19 ALL children and 19 healthy children who all had mild gingivitis. Two mL of saliva were collected and stored at âˆ’200Â°C. Then, salivary sIgA levels were measured using the ELISA method. Results: The results indicate an insignificant difference (p>0.05) in salivary sIgA levels between the ALL children in the maintenance phase with the level of 21.38 (7.23â€“107.26) and 37.26 (11.24â€“135.63) for the healthy children. Conclusion: There is no significant difference in salivary sIgA levels between the ALL children in the maintenance phase and the healthy children.